The Characteristic of Critical Genes in Neuroendocrine System and Their Regulation on Food Habit Transition and Metamorphosis of Veined Rapa Whelk Rapana venosa (Valenciennes, 1846) - Yang, Mei-Jie; Feng, Jie; Song, Hao; Yu, Zheng-Lin; Shi, Pu; Liang, Jian; Hu, Zhi; Zhou, Cong; Wang, Xiao-Lin; Zhang, Tao (Frontiers in Marine Science, 2021)
Metamorphosis is a critical developmental event in mollusks, and neuroendocrine system plays an essential role in this process. Rapana venosa is an economically important shellfish in China, but the artificial technology of R. venosa aquaculture is limited by metamorphosis. As a carnivorous gastropod, food habit transition makes the mechanism of R. venosa metamorphosis more complex. To investigate the changes in the neuroendocrine system and to reveal its role in regulating the food habit transition and metamorphosis of R. venosa, we cloned the cDNA sequences encoding 5-hydroxytryptamine receptor (Rv-5HTR), nitric oxide synthetase (Rv-NOS) and cholecystokinin receptor (Rv-CCKR), and investigated their expression by quantitative real-time PCR analysis, and explore the spatio-temporal changes of 5-HT protein expression using Immunohistochemical (IHC) analysis. The expression of the three geens was significantly increased in the early intramembrane veliger stage, which indicates that the three genes are related to the development of digestive system. Additionally, expression of the three genes was decreased after metamorphosis, while Rv-NOS and Rv-CCKR were increasingly expressed in competent larvae, which may help the larvae find suitable environments and promote digestive system development for metamorphosis, and the result of 5-HT IHC analysis also reflects the development of neuroendocrine system. Finally, based on the present results, we hypothesized that CCK and CCK receptor may be critical regulatory factors of food habit transition and metamorphosis. These results might provide information on the development of neuroendocrine system of R. venosa, and new insight into the regulation of the food habit transition and metamorphosis of gastropods.